Cerebral Malaria Causing Severe Sepsis, Acute Renal Failure, and Aspiration Pneumonia: A Case Report - Hoque, AMM Ehteshamul; Boksha, Shamim; Azad, Abul Kalam; Boque, Md Gofranul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
We report a case of severe malaria (cerebral malaria) developing aspiration pneumonia and acute renal failure in a 17year-old student after returning from malarial hyper endemic zone. The infecting organism was Plasmodium falciparum. Treatment with intravenous quinine and haemodialysis for kidney failure and broad spectrum antibiotic for aspiration pneumonia caused complete recovery of the patient. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.46 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 56-58